Ukraine-Russia War: Implications for Global Peace, Security and Development - Aisedion, Rufus; Agazuma, Ehigiamusor Solomon; Mohammed, Lawal Itakpe (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025DO - 10.58709/niujss.v11i2.2169, 2025)
This study examines the implications of the Ukraine-Russia war for global security, with a particular focus on the role of international bodies in promoting peace. Using the Realist theory of international relations as its theoretical framework, this study argues that the Ukraine-Russia conflict is a classic example of a security dilemma, where one state's efforts to increase its own security led to a decrease in the security of another state. The study employs a qualitative research method, with a focus on analyzing the implications of the Ukraine-Russia conflict for global security amongst others. The findings of this study suggest that international bodies, such as the United Nations, the Organization for Security and Co-operation in Europe, and the European Union, play a crucial role in promoting a ceasefire and peacebuilding in Ukraine. The study recommends that international bodies should play a more active role in promoting a ceasefire and peacebuilding in Ukraine, and that the international community should provide more economic and humanitarian assistance to Ukraine to help stabilize the country. The study also highlights the importance of mediation and diplomacy in peaceful conflict in the international community.  Finally, the paper further recommends that respect for a state’s sovereignty as enshrined in international law and United Nation’s charter should be a thing of national concern of both countries, that referendum should be considered especially with issues surrounding the status of Crimea.  Keywords:   Global Security, International Bodies, Peacebuilding, Development and Conflict.